Gluten-free wafer formulation: Development, characterisation and addition of flavourings with antioxidant capacity - Mantovano, Agostina (2022)
The incidence of celiac disease is increasing, therefore the demand for gluten-free products that also satisfy the nutritional requirements of celiac individuals is rising. Thus, the objective of the present work was to develop a gluten-free nutritionally balanced wafer formulation with a high content of antioxidants. First, the animal fat used in the traditional formulation was successfully replaced by high oleic sunflower. Second, the antioxidant content of several flavourings (cinnamon/honey/anise/vanilla) was measured and their addition to a gluten-free wafer formulation was evaluated. Third, multivariate statistical tools were used to select the formulation that properly mimicked the characteristics of a gluten-containing wafer. According to the results, anise and cinnamon were the most suitable flavourings to prepare gluten-free wafers, and the sensory analysis concluded that these formulations were highly acceptable (means>6.7 on the hedonic scale). Finally, the storage time analysis indicated that the texture of the gluten-free wafers was more susceptible to water absorption than gluten-containing wafers. Besides, cinnamon wafers presented a higher bioaccessible antioxidant capacity than anise wafers (43.5 ± 0.1 mg Trolox/g and 18.8 ± 0.9 mg Trolox/g respectively) (p < 0.05), which remained stable for four months. This indicates that during its shelf life, the product could be consumed with its beneficial effects intact.